Disease trajectory of SLE clinical endpoints and covariates affecting disease severity and probability of response: Analysis of pooled patient‐level placebo (Standard‐of‐Care) data to enable model‐informed drug development. (29th November 2022) - Goteti, Kosalaram; French, Jonathan; Garcia, Ramon; Li, Ying; Casset‐Semanaz, Florence; Aydemir, Aida; Townsend, Robert; Mateo, Cristina Vazquez; Studham, Matthew; Guenther, Oliver; Kao, Amy; Gastonguay, Marc; et al.
Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease affecting multiple organ systems. Many investigational agents have failed or shown only modest effects when added to standard of care (SoC) therapy in placebo‐controlled trials, and only two therapies have been approved for SLE in the last 60 years. Clinical trial outcomes have shown discordance in drug effects between clinical endpoints. Herein, we characterized longitudinal disease activity in the SLE population and the sources of variability by developing a latent disease trajectory model for SLE component endpoints (Systemic Lupus Erythematosus Disease Activity Index [SLEDAI], Physician's Global Assessment [PGA], British Isles Lupus Assessment Group Index [BILAG]) and composite endpoints (Systemic Lupus Erythematosus Responder Index [SRI], BILAG‐based Composite Lupus Assessment [BICLA], and Lupus Low Disease Activity State [LLDAS]) using patient‐level historical SoC data from nine phase II and III studies. Across all endpoints, in predictions up to 52 weeks from the final disease trajectory model, the following baseline covariates were associated with a greater decrease in SLE disease activity and higher response to placebo + SoC: Hispanic ethnicity from Central/South America, absence of hypocomplementemia, recent SLE diagnosis, and high baseline disease activity score using SLEDAI and BILAG separately. No discernible differences were observed in the trajectory of response to placebo + SoC across different SoC medications (antimalarial and immunosuppressant such as mycophenolate, methotrexate, and azathioprine). Across all endpoints, disease trajectory showed no difference in Asian versus non‐Asian patients, supporting Asia‐inclusive global SLE drug development. These results describe the first population approach to support a model‐informed drug development framework in SLE.